2002
DOI: 10.1021/la026435c
|View full text |Cite
|
Sign up to set email alerts
|

ABA-C15:  A New Dye for Probing Solvent Relaxation in Phospholipid Bilayers

Abstract: We synthesized and studied N-palmitoyl-3-aminobenzanthrone (ABA-C15), which we proved to be an advantageous new fluorescent phospholipid membrane label. While the absorption of ABA-C15 in protic solvents shows negative solvatochromism, its fluorescence emission is substantially red-shifted when the polarity of the solvent is increased. ABA-C 15 is excitable by lasers emitting in the range between 390 and 490 nm; it exhibits reasonable quantum yields in protic solvents and binds with high affinity to small unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…It has been shown that the spectral half width, i.e. the FWHM value passes through a maximum during the solvation process [32][33][34], which is in line with a nonuniform distribution of solvent response times [34,35].…”
Section: Time-dependent Fluorescence Shift (Tdfs)mentioning
confidence: 80%
“…It has been shown that the spectral half width, i.e. the FWHM value passes through a maximum during the solvation process [32][33][34], which is in line with a nonuniform distribution of solvent response times [34,35].…”
Section: Time-dependent Fluorescence Shift (Tdfs)mentioning
confidence: 80%
“…3-ABA was also the main metabolite of 3-NBA formed in human fetal bronchial cells and rat lung alveolar type II cells [7]. In addition, 3-ABA was found suitable for dyeing microporous polyethylene films, which are widely used for practical purposes such as separation of liquid mixtures, in particular, as separation membranes in chemical batteries [8], or to fluorescently label phospholipid membranes in the form of its N-palmitoyl derivative [9]. This suggests its industrial and/or laboratory utilization, leading to a putative exposure of people.…”
mentioning
confidence: 99%
“…One or two faster decay components, (s 1 , s 2 ), associated with the time-resolved uorescence decay monitored at the blue edge of the steady state uorescence spectrum becomes a rise component at the emission peak maximum (Table 1.) and at the red edge of the steady state uorescence spectrum. This is typical of solvation dynamics 11,[13][14][15] which is manifested by a time-dependent Stokes shi of the uorescence spectrum to the red (Fig. 4a-c).…”
Section: Time-resolved Uorescence Anisotropy Decaymentioning
confidence: 80%
“…Solvation dynamics is a powerful technique to probe relaxation dynamics of water molecules (hydration dynamics) associated with biomolecular surfaces and interfaces [11][12][13][14][15] where relaxation of the local environment of an optically excited uorophore is monitored by measurements of time-dependent uorescence Stokes shi (TDFSS). In the present work we have chosen a novel uorophore, 6-acetyl-(2-((4-hydroxycyclohexyl)(methyl)amino)naphthalene) 16 (ACYMAN, Scheme 1) to investigate hydration dynamics in the lipid-water interfaces of different DODAB/MO mixed vesicles, because, ACYMAN was found to be more suitable in probing water dynamics in micelle-water and protein-surfactant interfaces 14 compared to common solvation probes coumarin-500 (C500) and 4-dicyanomethylene-2-methyl-6-p-dimethylaminostyryl-4H-pyran (DCM).…”
Section: Introductionmentioning
confidence: 99%